Underlying structure of job competency scale in climate-smart agricultural extension service - Umar, Sulaiman; Man, Norsida; Mohd Nawi, Nolila; Abd. Latif, Ismail; Muktar, Bashir Garba (Universiti Putra Malaysia Press, 2019)
Climate change could reduce agricultural productivity in lower latitude communities, thereby threatening the food security and livelihoods of farm families. Climate smart agriculture (CSA) has been identified as an approach that could sustainably enhance productivity and mitigate the exacerbating effect of climate change on agriculture. For CSA technologies to be accepted, there is a need for special advisory services delivered by competent extension agents. This study assessed the structure of such competencies among 341 Malaysian extension workers selected randomly. The data obtained from a structured questionnaire was subjected to Varimax rotation of the principal component analysis. The KMO obtained was 0.847 while Bartlett's Test was significant (p < 0.001). Assessment of internal consistency revealed a Cronbach alpha of 0.926. Using Kaiser's criterion, seven components explaining 76.053% variance were extracted. However, parallel analysis streamlined and retained five components. This implied that CSA competency among Malaysian extension workers had a five component structure. This should be taken into consideration when designing trainings to make sure the relevant aspects are covered. It could also be beneficial in climate change adaptation and mitigation programmes.